Academic Burnout among Students studying in Selected Secondary School of Chitwan (MedS Alliance Journal of Medicine and Medical Sciences, 2022)
INTRODUCTION: Academic burnout has been widely reported in recent decades in different countries among students. Today’s students are facing dual stress in their academic endeavor i.e., higher academic expectations and perceived pressure from their parents. The aim of the study is to assess the level of academic burnout among the plus two students.MATERIAL AND METHODS: A cross-sectional study was done among secondary level students in a school of Bharatpur municipality. The study was conducted during October 2021 and December 2021among plus two level students. A self-administered questionnaire was used for data collection. Burnout was measured by using a 25 items tool comprising different types of burnout. Descriptive and inferential statistics were computed at 5% level of significant.RESULTS: Of total; 62.2% and 7.4% students had mild and moderate burnout respectively. Median value of total burnout was 56 out of the maximum value 125. There was strong significant correlation between personal and study related burnout, moderate significant correlation between personal and classmate related, and between personal and instructor related burn out. There was significance difference in the median personal burn out and instructor related burnout level among male and female students.CONCLUSIONS: High academic burnout was found among secondary level students. Intervention is required to address the burden.